The relationship between lifestyle/routine activities and worry about personal victimisation across months, days and moments - Engström, Alexander (Journal of criminology, 2025)
Drawing on a lifestyle-routine activity framework, this study explores associations between lifestyle/routine activities and worry about personal victimisation across months, days and moments. A bespoke smartphone application employing both traditional questionnaires and an Experience Sampling Method design was used by a convenience sample of students who responded to surveys regarding worry about victimisation. Lifestyle/routine activity measures showed varying associations with worry. The most consistent finding was that spending time with friends in the city-centre was significantly and negatively associated with worry across months and moments, but just failed to reach the level of significance for daily worry. Overall, the somewhat varying results indicate that worry cannot be assumed to be equally associated with lifestyle/routine activities across months, days and moments. These findings also imply more generally that research on worry about victimisation and other similar phenomena needs to consider how the outcome is measured in terms of reference periods and unit of analysis. Future research using more representative samples is needed to confirm the findings from this exploratory study.